2007
DOI: 10.4028/www.scientific.net/msf.550.211
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Strain Induced Precipitation during the Thermomechanical Processing of AA6111 Alloy

Abstract: The effect of interpass time during thermomechanical processing of AA61111 on flow behaviour and microstructure evolution has been investigated. This was achieved using plane strain compression testing undertaken on the Sheffield thermomechanical compression (TMC) facility, using the hit-hold-hit-quench approach. Following solution treatment at 560°C for 1200s, samples were water mist quenched to 320°C and deformed at a constant strain rate of 85s-1 to an initial strain of 0.5, unloaded and held for delay time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Also, previous research indicated that large plastic deformation can result in the formation of Mg 2 Si precipitates on dislocations in age-hardenable 6xxx alloys. [16,17] Hence, more Mg 2 Si precipitates are formed in the location with large plastic deformation. In extrusion 3 (Figure 1(c)), large localized deformation occurs in the streaked region, which is located in the thinner section neighboring the thicker section (web intersection).…”
Section: Effect Of Precipitationmentioning
confidence: 99%
“…Also, previous research indicated that large plastic deformation can result in the formation of Mg 2 Si precipitates on dislocations in age-hardenable 6xxx alloys. [16,17] Hence, more Mg 2 Si precipitates are formed in the location with large plastic deformation. In extrusion 3 (Figure 1(c)), large localized deformation occurs in the streaked region, which is located in the thinner section neighboring the thicker section (web intersection).…”
Section: Effect Of Precipitationmentioning
confidence: 99%
“…1 The heat-treatable AA6111 aluminium alloy has received significant interest from the automobile industries because it can be shaped after the heat solution treatment. 2 It possesses high strength and excellent stretch-forming characteristics. Using recycled aluminium alloys or developing an economical process is the best strategy to reduce the cost of producing aluminium alloy sheets.…”
Section: Introductionmentioning
confidence: 99%